Comparative Efficacy of D-Cloprostenol and DL-Cloprostenol on Cervical Dilatation after Detorsion in Buffaloes - Saini, G.; Singh, G.; Pandey, A. K.; Kumar, S.; Ravish, S. (The Indian Journal of Animal Reproduction, 2021)
This experiment deals with comparing efficacy of D-Cloprostenol and DL Cloprostenol on cervical dilatation after detorsion in buffaloes. 12 buffaloes after successful detorsion were divided into 2 groups and subjected to 2 different protocols for cervical dilatation. Based on the finding of the study, it was concluded that buffaloes treated with D-Cloprostenol showed better and early cervical dilatation as compared to buffaloes administered with DL-Cloprostenol.